Defect‐Stabilized Triplet State Excitons: Toward Ultralong Organic Room‐Temperature Phosphorescence. (13th November 2018) - Shi, Wenying; Yao, Jian; Bai, Liqian; Lu, Chao
Abstract: Generation of organic room‐temperature phosphorescent (RTP) with high efficiency and long lifetime has encountered great obstacles because the luminescence process of long‐lived excitons generally involves the conversion of the spin‐allowed singlet excitons to the spin‐forbidden triplet excitons. In contrast, the lifetime and efficiency of inorganic RTP materials are often superior to those of organic materials, because their luminescence derives from gradual release of trapped charge carriers from isolated traps (defects). Such a trapping–detrapping mechanism inspires one to take advantage of the defects of inorganic materials for stabilizing triplet state excitons and enhancing RTP performances of organic materials (e.g., carbon dots, CDs). Based on the above principle, as‐prepared CDs‐based material shows ultralong RTP lifetime of about 800 ms under ambient conditions. Interestingly, in this system the appearance of the tunneling‐related exciton transfer process assists the acquisition of long‐lived phosphorescence. The designed organic–inorganic RTP composite builds a bridge between organic and inorganic luminescence mechanisms. Abstract : A basic design rule for extending the exciton lifetime of organic materials is presented, which involves stabilization of the triplet state excitons of organic molecules through the defect of the inorganic matrix. This strategy offers an important step in the construction of advanced room temperature phosphorescence materials.